Hypoxic Transformation of Immune Cell Metabolism Within the Microenvironment of Oral Cancers - Chaudhary, Amrita; Bag, Swarnendu; Arora, Neeraj; Radhakrishnan, Vivek S.; Mishra, Deepak; Mukherjee, Geetashree (Frontiers in Oral Health, 2020)
Oral squamous cell carcinoma (OSCC) includes tumours of the lips, tongue, gingivobuccal complex, and floor of the mouth. Prognosis for OSCC is highly heterogeneous, with overall 5-year survival of approximately 50%, but median survival of just 8–10 months for patients with locoregional recurrence or metastatic disease. A key feature of OSCC is microenvironmental oxygen depletion due to rapid growth of constituent tumour cells, which triggers hypoxia-associated signalling events and metabolic adaptations that influence subsequent tumour progression. Better understanding of leukocyte responses to tissue hypoxia and onco-metabolite expression under low-oxygen conditions will therefore be essential to developing more effective methods of diagnosing and treating patients with OSCC. This review assesses recent literature on metabolic reprogramming, redox homeostasis, and associated signalling pathways that mediate crosstalk of OSCC with immune cells in the hypoxic tumour microenvironment. The likely functional consequences of this metabolic interface between oxygen-starved OSCC and infiltrating leukocytes are also discussed. The hypoxic microenvironment of oral squamous cell carcinoma modifies redox signalling and alters the metabolic profile of tumour-infiltrating immune cells. Improved understanding of heterotypic interactions between host leukocytes, tumour cells, and hypoxia-induced onco-metabolites will inform the development of novel theranostic strategies for OSCC.